Kehidupan Penyintas Kekerasan dalam Rumah Tangga Pasca Terminasi Layanan - Haiyun Nisa; Amrina Habibi; Abdullah Abdul Muthaleb (Kafa`ah: Journal of Gender Studies, 2019)
Women survivors on domestic violence (KDRT) who access services at integrated service of women and children protection (P2TP2A) District / City in Aceh Province get holistic services for handling the cases they experience. The comprehensive service provided is able to help some survivors resolve the problem until it is complete and experience the termination process (termination of service), but not a few survivors who no longer continue accessing services so that they also experience a termination process. After termination, various dynamics of life experienced by survivors related to the violence they experienced. This is the background of this research, so that it aims to find out the lives of women survivors of domestic violence in the individual, family and social post-termination services at P2TP2A. This study uses a qualitative approach with narrative methods. Data collection is done by observation and interview techniques. The participants involved in this study were 50 women survivors of domestic violence who had accessed services at P2TP2A after termination. The results obtained from this study are that some survivors are able to see themselves more positively, have the motivation to experience positive changes in their lives, the presence of psychosocial reinforcement from the family and the environment. However, some of the other survivors remained in the domestic violence cycle, despite feeling discomfort. The new findings obtained in this research process are survivors who are reporters and pioneers in handling cases of domestic violence.